“The Economics of Adjustment and Growth” de Pierre-Richard Agenor - Blumenschein, Fernando (Estudos Econômicos (São Paulo), 2000)
Resenha Bibliográfica do livro “The Economics of Adjustment and Growth” de Pierre-Richard Agenor